DNA Damage, Oxidative Stress and Related Metabolic By-Products in Cancer and Environmental Studies - Peluso, Marco E. M.; Galli, Andrea; Mello, Tommaso (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Computational fluid dynamics (CFD), which uses numerical analysis to predict and model complex flow behaviors and transport processes, has become a mainstream tool in engineering process research and development. Complex chemical processes often involve coupling between dynamics at vastly different length and time scales, as well as coupling of different physical models. The multiscale and multiphysics nature of those problems calls for delicate modeling approaches. This book showcases recent contributions in this field, from the development of modeling methodology to its application in supporting the design, development, and optimization of engineering processes.